El sistema de información geográfica: un instrumento para la planificación y gestión urbana - Pueyo Campos, Ángel (Geographicalia, 2017)
GIS have been proved as the new ideal tools for urban planification and management. They bridge the real world and its interlocutor, urban technitian; they improve our knowledge of reality and help us in our tasks of organising, spatialising and normalising the information coming how this same real world. They also facilitare the graphic representation of this reality and make easier the insertion of models and informative questions. All this will decisively benedit the efectivity and performance in our reaching of decisitions.